Broadband quad‐polarisation reconfigurable antenna. Issue 21 (1st October 2018) - Cui, Y.H.; Zhang, P.P.; Li, R.L.
Abstract : A new broadband quad‐polarisation reconfigurable antenna is proposed. The reconfigurable antenna consists of a +45° polarised dipole and a −45° polarised dipole. Each dipole is excited by a broadband balun. A reconfigurable feeding network is employed to feed the ±45° polarised dipoles. When the ±45° polarised dipoles are separately fed, ±45° linear polarisations are obtained. As the ±45° polarised dipoles are simultaneously fed with a +90° or −90° phase difference, left‐handed circular polarisation (CP) or right‐handed CP is asserted. It is shown by simulation and experiment that the quad‐polarisation reconfigurable antenna achieves an overlapped impedance bandwidth of 37% (0.69–1.0 GHz) for return loss >15 dB and an overlapped bandwidth of 36% (0.66–0.95 GHz) for axial ratio <3 dB.